PERAN SANGGAR PENYEWAAN BAJU TARI SEBAGAI SARANA EDUPRENEURSHIP DALAM PENDIDIKAN SENI DAN BUDAYA - Bintan Tiska Amalia; Asna Mqashida Kholiza; Annisa Azzahra Dewi; Sahrul Akmal Mufti (JIP: Jurnal Ilmu Pendidikan, 2025)
Art and cultural education play an important role in shaping one’s personality, enhancing creativity, and preserving the nation’s traditional cultural values. Over time, art has evolved not only as a medium for self-expression and cultural preservation but also as a means to develop the creative economy, particularly through the concept of edupreneurship. This study aims to analyze the role of dance costume rental studios as a medium for edupreneurship in the field of art and cultural education. The research problem focuses on how dance costume rental activities can integrate educational and entrepreneurial values within the community. This study was conducted at ARH Dance Management Studio, located in Wonopringgo District, Pekalongan Regency, using a descriptive qualitative method. Data were collected through interviews, observations, and literature studies. The results show that the studio functions as a non-formal educational institution that teaches artistic skills while fostering entrepreneurial spirit. Through costume rental activities, training, and collaboration with the local community, the studio successfully promotes independence, responsibility, and appreciation for local culture. Moreover, these activities also provide positive economic and social impacts on the surrounding community.